1975
DOI: 10.1093/bja/47.6.730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercostal Nerve Blockade During Operation on Lung Function and the Relief of Pain Following Thoracotomy

Abstract: The use, during operation, of intercostal nerve blocks with lignocaine and bupivacaine for the relief of pain following thoracotomy was assessed in 138 patients. Irrespective of the method used to evaluate efficacy, it was not possible to demonstrate a lasting effect of clinical significance favouring either local anaesthetic agent. This form of treatment, although free from serious side effects, had no beneficial effects on lung function and is not recommended for the relief of pain following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 0 publications
0
23
0
2
Order By: Relevance
“…on pain and ventilation have been reported in other studies. Most authors have found the method very satisfactory (20,21,26,40), but a few have reported little advantage over treatment with centrally acting analgesics (42,43). These discrepancies might, as in the present study, be due to differences in the type of incision and surgery, and to whether a uni-or bilateral block has been applied, but might also be explained by differences in the site of blocking of the intercostal nerves.…”
Section: Fevr/fvc (Yo)mentioning
confidence: 46%
“…on pain and ventilation have been reported in other studies. Most authors have found the method very satisfactory (20,21,26,40), but a few have reported little advantage over treatment with centrally acting analgesics (42,43). These discrepancies might, as in the present study, be due to differences in the type of incision and surgery, and to whether a uni-or bilateral block has been applied, but might also be explained by differences in the site of blocking of the intercostal nerves.…”
Section: Fevr/fvc (Yo)mentioning
confidence: 46%
“…Delilkan and others (1973) and Faust and Nauss (1976) showed that intercostal block gave better analgesia and caused less hypercarbia than did opiate analgesia. Conversely, Galway, Caves and Dundee (1975) found that intercostal block was ineffective, and that there was no difference in Pa^ values between patients receiving intercostal block and controls. Presumably, this is because both groups of patients received opiates, whereas probably only the control group had received opiates at the time that •Pa C02 values were measured in the former studies.…”
Section: Discussionmentioning
confidence: 88%
“…Retention of carbon dioxide is more severe in patients with spirometric evidence of emphysema (Swenson, StallbergStenhagen and Beck, 1961) and is possibly more severe if lung tissue is resected (Pandit, Galway and Dundee, 1973). Patients recovering from thoracotomy are more sensitive to the respiratory depressant effects of opiates than are patients recovering from upper abdominal surgery (Galway, 1972). Delilkan and others (1973) and Faust and Nauss (1976) showed that intercostal block gave better analgesia and caused less hypercarbia than did opiate analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…By this way, spinal nerves from T1 through T 11 can be blocked effectively decreasing VAS pain scores significantly. Local anesthetics can be infused as a single dose just before closure of the thoracotomy (11,(33)(34)(35)(36), as a single (37) or multiple (38) percutaneous injections or via an indwelling intercostal catheter (39)(40)(41). Intercostal blockade can reduce opioid requirements, however, cannot eliminate them.…”
Section: Intercostal Blockadementioning
confidence: 99%